PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJAPEGAWAI STUDI PADA PT. PLN (PERSERO) DISTRIBUSI JATENG DAN DIY JATINGALEH - Rabeka Puri Rahayu, 11.05.51.0068 (Students Journal of Economic and Management, 2015)
This study aims to examine the effect of compensation, work discipline and motivation on employee performance. This research was conducted at PT.PLN (Persero) Distribution of Central Java and Yogyakarta Jatingaleh. The sampling method used purposive sampling with the criteria of a permanent employee of PT.PLN (Persero) Distribution of Central Java and Yogyakarta Jatingaleh and are given permission to fill out a questionnaire. The number of shares based samples taken by the opinions Uma Sekaran (2000) which states that an adequate sample size for a study is more than 30 and less than 200. The relationship between variables and or effect described by the method of analysis multiple regression. The results showed that compensation, work discipline, and motivation has positive and significant effect on employee performance. So if compensation, discipline and motivationis getting better, it will better the performance of employees generated. Keywords: Compensation, Work Discipline, Motivation, and Employee Performance